Um Japão inventado para o consumo no BL: características genéricas e adaptações para o contexto brasileiro em Vitral - Kushima, Fernanda Muto (2018)
The Japan created for consumption refers to the imagery forged about Japan from the engendering of specific discursive strategies (GREINER, 2016). This imagery, once created by the West and currently exported by Japan itself, provides several models to be followed for something to have the "made in Japan" stamp. In this way, many media that wish to approach this "aesthetic", use these models to signify and re-significate their productions. Based on these assumptions, the objective of this research is to study the narrative strategies used in the Brazilian BL manga entitled Vitral, having the models girl-for-consumption and love-for-consumption as its thematic axes. The genre BL (Boy's Love) refers to works whose narrative focus is the love and / or sexual relationship between two male characters, targeting women as the main audience. For this, we will use as theoretical and methodological assumptions the Umberto Eco's concepts of "Model Author" and "Model Reader", in order to understand what remains of this Japanese imaginary for consumption and what escapes the expected model in the themes of girls and love. Accordingly, we will also analyze the conventions that these specific models engender from the interweaving of the cultural elements to the discursive elements, present in the construction strategies of Vitral's "Model Reader", in order to understand in a more detailed way some of the elements present in the dynamics between communication and consumption.